2005
DOI: 10.1536/ihj.46.927
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Primary Cardiac Lymphoma With Atrioventricular Nodal Block

Abstract: SUMMARYA 69-year-old female suffering from third-degree atrioventricular block with syncope underwent permanent pacemaker implantation. However, she developed shortness of breath 2 months after the implantation. Blood tests revealed elevated levels of LDH, CRP, BNP, and SIL-2R. Transthoracic echocardiography showed thickened left and right atrial walls with mild pericardial effusion. A diagnosis was made based on a CT scan and histology. Although most primary cardiac malignant lymphomas are associated with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Chemotherapy, immuno-chemotherapy, stem cell transplant, radiation therapy and combined modality approaches have been used to treat PCL. 7,8,[11][12][13][14] Recent reviews have attempted to assess CR rates using these various approaches in PCL. 7,8 Traditionally, PCL is thought to have an extremely poor prognosis due to life-threatening complications, such as cardiac rupture, which can occur at diagnosis or during treatment due to the anatomical location of the tumor.…”
Section: Utility Of Multimodality Imaging In Diagnosis and Managementmentioning
confidence: 99%
“…Chemotherapy, immuno-chemotherapy, stem cell transplant, radiation therapy and combined modality approaches have been used to treat PCL. 7,8,[11][12][13][14] Recent reviews have attempted to assess CR rates using these various approaches in PCL. 7,8 Traditionally, PCL is thought to have an extremely poor prognosis due to life-threatening complications, such as cardiac rupture, which can occur at diagnosis or during treatment due to the anatomical location of the tumor.…”
Section: Utility Of Multimodality Imaging In Diagnosis and Managementmentioning
confidence: 99%
“…1,3,[6][7][8] Primary cardiac lymphoma is diffi cult to diagnose clinically because of its nonspecifi c clinical manifestations. 1,3,4 Noninvasive imaging methods such as TTE, CT, and MRI have allowed early, correct detection of primary cardiac malignancies. 1,3,6,8,9 Ceresoli et al 9 reported that the sensitivities of TTE, CT, and MRI for detecting primary cardiac lymphoma were 55%, 71%, and 92%, respectively.…”
Section: Case Reportmentioning
confidence: 99%
“…1,3 Symptoms range from those mimicking angina, congestive heart failure, or pericarditis to heart block and sudden death. 1,3,4 Therefore, early and correct diagnosis is important for patient management, and radiologists should be familiar with its imaging fi ndings. We describe a case of a 76-year-old woman with a primary cardiac lymphoma who was successfully treated with surgery and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, normal sinus rhythm with normal AV conduction can be achieved by chemotherapy, without permanent pacemaker implantation. 1,[14][15][16] In the present case, AV conduction disturbance did not resolve and permanent pacemaker implantation was necessary. The tumor location, tumor infiltration and interval of starting therapy might be affected.…”
mentioning
confidence: 99%